2018
DOI: 10.1111/his.13656
|View full text |Cite
|
Sign up to set email alerts
|

The role of transbronchial cryobiopsy in lung transplantation

Abstract: Transbronchial cryoprobe bronchoscopy allows the harvesting of larger and more expanded lung tissue samples, increasing the diagnostic yield in the monitoring of the lung allograft by means of a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Lastly, the diagnostic use of cryobiopsies in lung allografts increases the amount of tissue obtained and thus potentially improves the diagnostic yield. However, their universal implementation should be critically discussed considering the increased risks of bleeding and air leakage 32 …”
Section: Bronchiolitis Obliterans Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the diagnostic use of cryobiopsies in lung allografts increases the amount of tissue obtained and thus potentially improves the diagnostic yield. However, their universal implementation should be critically discussed considering the increased risks of bleeding and air leakage 32 …”
Section: Bronchiolitis Obliterans Syndromementioning
confidence: 99%
“…PPFE, however, is a terminology mostly utilized to describe a radiologic pattern, whereas the more accurate histologic description of the observed pattern of predominant subpleural and paraseptal collagenous obliteration of the alveoli with elastosis is AFE. Analogous to BO, AFE could also be shown to be a general reaction to injury, which can arise due to viral or bacterial infection, but also following acute AMR, leading to a sequence of vascular and epithelial injury, intra‐alveolar fibrinous exudation, aberrant macrophage accumulation and activation, failed fibrin degradation, and ultimately fully developed AFE 25,32 . The relevance of fibrin deposition is provided by a study of Paraskeva et al, who demonstrated that acute fibrinoid organizing pneumonia (AFOP), an injury pattern defined by mesenchymal proliferation, loosely intermixed with fibrin and absence of interstitial fibrosis, is an important predictor of inferior posttransplant outcome 34 .…”
Section: Restrictive Allograft Syndromementioning
confidence: 99%
“…Twenty-two percent of fTBB were nondiagnostic, versus 2.5% of TBLCB (p ¼ 0.014), and acute and chronic rejection were more frequently diagnosed in TBLCB (p ¼ 0.0657 and p ¼ 0.0053, respectively). 51 Yarmus et al reported their experience with 21 consecutive cases where TBLCB was able to obtain larger amounts of higher quality tissue with significantly less crush artifact and no significant complications. 52 Fruchter et al described their initial experience with 40 patients who underwent TBLCB (27 for routine postlung transplantation surveillance and 13 for clinically indicated bronchoscopy) compared with 40 matched controls.…”
Section: Tblcb Diagnostic Yield In Other Indicationsmentioning
confidence: 99%
“…7,37,38,52 In parallel, the use of artificial airways varies widely ranging from a bite block with conscious sedation, laryngeal mask airway, endotracheal intubation with and without paralysis, and mechanical ventilation as well as rigid bronchoscopy (RB). 2,7,29,31,51,62 The only review that directly comments on the DY and complication rate of different sedation and airway management techniques was by Ravaglia et al in their meta-analysis of 11 studies reviewing 625 cases. 7 The DY was not adversely affected in nonintubated patients undergoing conscious sedation.…”
Section: Sedation and Airway Managementmentioning
confidence: 99%
See 1 more Smart Citation